Histone variant macroH2A1 rewires carbohydrate and lipid metabolism of hepatocellular carcinoma cells towards cancer stem cells. Issue 8 (3rd August 2018) - Lo Re, Oriana; Douet, Julien; Buschbeck, Marcus; Fusilli, Caterina; Pazienza, Valerio; Panebianco, Concetta; Castracani, Carlo Castruccio; Mazza, Tommaso; Li Volti, Giovanni; Vinciguerra, Manlio
ABSTRACT: Hepatocellular carcinomas (HCCs) contain a sub-population of cancer stem cells (CSCs) that are responsible for tumor relapse, metastasis, and chemoresistance. We recently showed that loss of macroH2A1, a variant of the histone H2A and an epigenetic regulator of stem-cell function, in HCC leads to CSC-like features such as resistance to chemotherapeutic agents and growth of large and relatively undifferentiated tumors in xenograft models. These HCC cells silenced for macroH2A1 also exhibited stem-like metabolic changes consistent with enhanced glycolysis. However, there is no consensus as to the metabolic characteristics of CSCs that render them adaptable to microenvironmental changes by conveniently shifting energy production source or by acquiring intermediate metabolic phenotypes. Here, we assessed long-term proliferation, energy metabolism, and central carbon metabolism in human hepatoma HepG2 cells depleted in macroH2A1. MacroH2A1-depleted HepG2 cells were insensitive to serum exhaustion and showed two distinct, but interdependent changes in glucose and lipid metabolism in CSCs: (1) massive upregulation of acetyl-coA that is transformed into enhanced lipid content and (2) increased activation of the pentose phosphate pathway, diverting glycolytic intermediates to provide precursors for nucleotide synthesis. Integration of metabolomic analyses with RNA-Seq data revealed a critical role for the Liver X Receptor pathway, whose inhibition resulted in attenuated CSCs-like features. These findings shed light on the metabolic phenotype of epigenetically modified CSC-like hepatic cells, and highlight a potential approach for selective therapeutic targeting.